The Use of Grounded Theory to discover organizational indifferences in University of Brawijaya - Abusharbeh, Mohmad Tawfiq (Jurnal Aplikasi Manajemen, 2013)
This paper uses of grounded theory approach as away of handling problematic of employees behavior in organization work, Managerial carelessness is the central phenomenon expressed a sets of actions and interactions that polluting organizational atmosphere. On the other hand may be its job unhealthiness, that leads employees tried to avoid or not accepted responsibility inside their organization work. This approach is illustrated in the context of organization research based on two cases of grounded theory analysis (a) study of face to face interaction in a university between employees. (b) Shape organizational indifferences. This paper investigated with the main conditions that cause managerial carelessnessin University of Brawijaya and make employees ready to leave organization. The paper concluded some propositions that discovered organizational indifferences by using Grounded theory.